The acrocallosal syndrome and Greig syndrome are not allelic disorders. - Brueton, L A (1992)
Acrocallosal syndrome is an autosomal recessive form of polysyndactyly associated with mental retardation and agenesis of the corpus callosum. There have been suggestions that it is allelic to the Greig cephalopolysyndactyly syndrome. Linkage analysis, using flanking markers, shows this suggestion is unlikely to be correct.